Indirect and direct effects of salinity on the quantity and quality of total amino acids in Ulva ohnoi (Chlorophyta). Issue 3 (27th April 2015) - Angell, Alex R.; Mata, Leonardo; de Nys, Rocky; Paul, Nicholas A.; Buschmann, A.
<x xml:space="preserve">Abstract</x> Salinity can affect the quantity and quality of total amino acids (TAAs) in seaweeds indirectly by altering growth rates and thereby diluting or concentrating the amino acid content of the biomass, or directly by altering the synthesis of specific amino acids and osmolytes. This study attempted to partition the indirect and direct effects of salinity on the quantity and quality of TAAs in the green seaweed Ulva ohnoi by culturing it under a range of salinities without nutrient limitation. Both the quantity and quality of TAAs varied across the salinity treatments. Quantity was most strongly related to the growth rate of the seaweed and was highest in the slowest growing seaweed. In contrast, the quality of TAAs (individual amino acids as a proportion of total content) was most strongly related to salinity for all amino acids, although this varied substantially among individual amino acids. Increases in salinity were positively correlated with the proportion of proline (46% increase), tyrosine (36% increase), and histidine (26% increase), whereas there was a negative correlation with alanine (29% decrease). The proportion of methionine, with strong links to the synthesis of the osmolyte dimethylsulfoniopropionate, did not correlate linearly with salinity and instead was moderately higher at the optimal salinities for growth. These results show that salinity simultaneously affects the quantity and quality of TAAs in seaweed through both indirect and direct mechanisms, with growth rates playing the overarching role in determining the quantity of TAAs.